6(4a+12)=8(3s-14)

Simple and best practice solution for 6(4a+12)=8(3s-14) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(4a+12)=8(3s-14) equation:


Simplifying
6(4a + 12) = 8(3s + -14)

Reorder the terms:
6(12 + 4a) = 8(3s + -14)
(12 * 6 + 4a * 6) = 8(3s + -14)
(72 + 24a) = 8(3s + -14)

Reorder the terms:
72 + 24a = 8(-14 + 3s)
72 + 24a = (-14 * 8 + 3s * 8)
72 + 24a = (-112 + 24s)

Solving
72 + 24a = -112 + 24s

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-72' to each side of the equation.
72 + -72 + 24a = -112 + -72 + 24s

Combine like terms: 72 + -72 = 0
0 + 24a = -112 + -72 + 24s
24a = -112 + -72 + 24s

Combine like terms: -112 + -72 = -184
24a = -184 + 24s

Divide each side by '24'.
a = -7.666666667 + s

Simplifying
a = -7.666666667 + s

See similar equations:

| (6x-6)=24 | | 2e^4x-2=2 | | 16-7y+14=3y+14-7 | | F-8=6+3f | | 2+r=2-7r | | 9.2+3.1=2.06+1.15x | | -7-7(-5n-5)=4(5n-7)-4 | | 49y=12(4y+12) | | w+-8=6 | | (2y+2)-(y+6)= | | 0=16t^2-300t+1000 | | 8(e-5)=2(3e-8) | | -1.5(-4.7)-4.7= | | 19-3n=-29 | | 14-x=-10 | | 3a+8=y | | -4j-2(3j+5)=-6j+2(j+2) | | 104=8(v+6) | | 4-3=2+8 | | 7x-750=5x-600 | | 3x-6(5+x)=-4(x+7) | | 6-6=9x+5x | | 2d+18=12-6(d+7) | | -1.5(-1.5)-4.7= | | -(-x)x=96 | | 10x=4x-28 | | 4.1(1-5.8v)=3.5v-14.996 | | -a+2b-8a= | | [2/3x-2/3]=2/3 | | 4j-2(3j+5)=-6j+2(j+2) | | -1.5x-1.5-4.7= | | 17y-13y=20 |

Equations solver categories